2023
DOI: 10.1007/s11005-022-01628-w
|View full text |Cite
|
Sign up to set email alerts
|

Coloured $$\mathfrak {sl}_r$$ invariants of torus knots and characters of $${\mathcal {W}}_r$$ algebras

Abstract: We show that the characters of slr versions of the (1, p) singlet and the (1, p) triplet VOAs arise as limits of appropriately coloured slr Jones invariants of certain torus links.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…Our proofs use the formula for these invariants given by Lin and Zheng in [23], and further use combinatorial results to match the limits with appropriate VOAs. Unlike the case of principal W algebras that make appearance in relation to the knots T (p , p) [20], the characters of the singlet and triplet VOAs are either not modular invariant (in the former case) or some modifications are necessary (for the latter case). Their analytic properties have been much studied recently, see for instance [13], [8], [9], [7], etc.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Our proofs use the formula for these invariants given by Lin and Zheng in [23], and further use combinatorial results to match the limits with appropriate VOAs. Unlike the case of principal W algebras that make appearance in relation to the knots T (p , p) [20], the characters of the singlet and triplet VOAs are either not modular invariant (in the former case) or some modifications are necessary (for the latter case). Their analytic properties have been much studied recently, see for instance [13], [8], [9], [7], etc.…”
Section: Introductionmentioning
confidence: 97%
“…It is now natural to ask if characters of other VOAs may also similarly arise as appropriate limits of quantum invariants of knots and links. Indeed, in a previous article [20], it was shown that the characters of the principal W-algebras based on sl r for all r ≥ 2 arise as limits of sl r invariants of torus knots. These particular VOAs enjoy very special properties.…”
Section: Introductionmentioning
confidence: 99%